Optimization of Ethanol Production via an Adsorption Process Using Molecular Sieve 3A with the Differential Experts Method - Syahwaliza Chaniatul Chabibbah; Akhmad Syafiq Hasbi; Ni Ketut Sari; Ika Nawang Puspitawati; Ely Kurniati; Sintha Soraya Santi (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
Ethanol has significant potential as a renewable energy source that can be utilized as an environmentally friendly alternative fuel. However, ethanol produced by conventional distillation still reaches a maximum purity of only 95–96% due to the formation of an ethanol–water azeotrope, requiring further purification to obtain fuel-grade ethanol. This study aimed to enhance ethanol purity via adsorption distillation with a 3A molecular sieve and to determine the optimal operating conditions using Response Surface Methodology (RSM). The research variables consisted of 3A molecular sieve weights of 20, 40, 60, 80, and 100 grams, as well as reflux ratios of 0.2, 0.4, 0.6, 0.8, and 1 mL/s. The adsorption distillation process was conducted at 78°C using an adsorption distillation apparatus. Experimental data were analysed using Design-Expert 13 software using a Central Composite Design (CCD) with 11 experimental runs. The results showed that increasing the molecular sieve weight and reflux ratio positively affected ethanol concentration. The optimum condition was achieved at a molecular sieve weight of 100 grams and a reflux ratio of 1 mL/s, resulting in an ethanol concentration of 99.9% with a desirability value of 1.000. These findings indicate that the 3A molecular sieve is effective in improving ethanol purity to meet the fuel-grade standard specified in SNI 7390:2012. Contribution to Sustainable Development Goals (SDGs):SDG 7 – Affordable and Clean EnergySDG 6: Clean Water and SanitationSDG 9: Industry, Innovation and InfrastructureSDG 13 – Climate Action